2016
DOI: 10.3399/bjgp16x686089
|View full text |Cite
|
Sign up to set email alerts
|

Emergency hospital admissions for asthma and access to primary care: cross-sectional analysis

Abstract: Background: Access to general practices may be an important determinant of emergency admissions for asthma, as early treatment of exacerbations has been shown to prevent deterioration. Aim: To determine whether access to primary care is associated with emergency admissions for asthma. Design and Setting: Cross-sectional analysis of data from English practices in 2010/11. Method: Negative binomial regression was used to explore the associations between emergency admissions for asthma and seven measures of patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Such associations have been consistently observed, for example, in a previous study that reported that improving timely access to primary care for early treatment of exacerbations resulted in a lower rate of emergency admissions for asthma. 23 …”
Section: Discussionmentioning
confidence: 99%
“…Such associations have been consistently observed, for example, in a previous study that reported that improving timely access to primary care for early treatment of exacerbations resulted in a lower rate of emergency admissions for asthma. 23 …”
Section: Discussionmentioning
confidence: 99%
“…These studies focused on specific conditions such as asthma,31 chronic obstructive pulmonary disease25 and heart failure 26. Practices with higher scores on GPPS measures related to access had lower adjusted admission rates in all but one study, though the exact measure(s) showing this association is inconsistent across studies.…”
Section: Discussionmentioning
confidence: 99%
“…We did not observe significant relationships between asthma QOF scores and admission rates, suggesting that annual reviews alone may not be sufficient to reduce admissions. Purdy et al also found no association between QOF scores and admissions,2 while Fleetcroft et al found that improved access to General Practice was associated with reduced asthma admissions 10. Better primary care management of asthma is likely to reduce admissions, but QOF metrics may not capture the key drivers of this improvement.…”
Section: Discussionmentioning
confidence: 99%